(-)-baclofen and gamma-aminobutyric acid inhibit calcium currents in isolated retinal ganglion cells. - Bindokas, V P (1991)
Of the various synaptic inputs known to converge upon retinal ganglion cells, the major inhibitory inputs are thought to be GABAergic. Although gamma-aminobutyric acid (GABA) is known to activate anion-selective ion channels in retinal ganglion cells, we have tested the possibility that GABA can also modulate cationic conductances in these cells, as seen in other central and peripheral neurons. Specifically, we have made whole-cell patch-clamp recordings to test whether voltage-gated calcium currents in isolated goldfish retinal ganglion cells are sensitive to GABAB receptor ligands. (-)-Baclofen and GABA inhibited calcium currents activated by moderately long depolarizations and, during large depolarizations (e.g., to 0 mV), also appeared to accelerate the rate of current decay. The calcium current inhibition induced by (-)-baclofen and GABA was not prevented by 2-hydroxysaclofen, phaclofen, or bicuculline, even though bicuculline suppressed a GABA-activated conductance in these cells. These results demonstrate the presence of baclofen- and GABA-sensitive calcium currents in vertebrate retinal ganglion cells as well as the coexistence of GABAA and GABAB receptors in individual retinal ganglion cells.